Strategies for controlling the degradation of grasslands invaded by Sporobolus indicus (L) R. Br - Padilla, C?sar; Sardi?as, Yurangel; Febles, Gustavo; Fraga, Nidia (Cuban Journal of Agricultural Science, 2013)
Results of studies conducted in the Institute of Animal Science of the Republic of Cuba with an integral and multidisciplinary approach are presented. The topic developed is related with the applied strategies to control the degradation of grasslands invaded by wire grass (Sporobolus indicus). Other researches conducted with this weed in different tropical and subtropical regions considering the biological characteristics of this species are also considered. Reproduction methods of wiregrass and of seeds production are also dealt with. The negative effect of this weed on the economy and biomass production of an improved grassland is analyzed. The infestation level of wiregrass and the pureness percentage of the improved pasture are considered, as well as the application of recovery alternatives throughout new sowings or rehabilitation. It is proved that planting species of the Pennisetum genus by the plowing method or the traditional method are effective ways of control that also favor the recovery of completely damaged grasslands. The recovery or rehabilitation with the use of plowing plus harrowing, in combination with the chemical and organic fertilization, is a promising alternative to recover the energy of the grassland and an option to minimize the population of this weed and reestablish the productivity of the agroecosystem. A good animal and agrotechnical management is suggested after these labours, in order to achieve the sustainability of the improved pastures. The knowledge described will make possible to design a program for the integral control of the weed and the recovery of improved grasslands ecosystems invaded by wiregrass. Key words: Sporobolus indicus, weed, sowing, rehabilitation.